2007
DOI: 10.1016/j.idairyj.2006.05.013
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced production of pediocin PA-1 in wild nisin- and non-nisin-producing Lactococcus lactis strains of dairy origin

Abstract: In this work, heterologous production of pediocin PA-1 in Lactococcus lactis ESI 153 and ESI 515 (Nis + ), two strains selected because of their technological properties for cheesemaking, was achieved after transformation with plasmids pMC117, pRK119 and pCNC1, which contain the complete pediocin operon under the control of the strong P32 promoter. The pediocin production of the L. lactis ESI 153 derivatives containing pRK119 or pCNC1 was higher (approximately 165%) than that achieved by the natural pediocin P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Heterologous expression is an efficient strategy to enhance bacteriocin production yields. The lactic acid bacterium Lactococcus lactis was successfully used to produce bacteriocins (Rodríguez et al ., ) including pediocin PA‐1 (Horn et al ., 1998; 1999; 2004; Reviriego et al ., 2005; 2007a,b; Martín et al ., ; Arqués et al ., ), and could therefore be used as a host for large‐scale production. Besides, due to its generally recognized as safe status, L. lactis is an interesting bacterium for in vivo delivery of bacteriocins for probiotic purpose (Osmanagaoglu et al ., ; Pontes et al ., ; Dobson et al ., ) or in fermented food (Renye and Somkuti, ).…”
Section: Introductionmentioning
confidence: 99%
“…Heterologous expression is an efficient strategy to enhance bacteriocin production yields. The lactic acid bacterium Lactococcus lactis was successfully used to produce bacteriocins (Rodríguez et al ., ) including pediocin PA‐1 (Horn et al ., 1998; 1999; 2004; Reviriego et al ., 2005; 2007a,b; Martín et al ., ; Arqués et al ., ), and could therefore be used as a host for large‐scale production. Besides, due to its generally recognized as safe status, L. lactis is an interesting bacterium for in vivo delivery of bacteriocins for probiotic purpose (Osmanagaoglu et al ., ; Pontes et al ., ; Dobson et al ., ) or in fermented food (Renye and Somkuti, ).…”
Section: Introductionmentioning
confidence: 99%
“…Lactococcus lactis FI10486 has the ability to coproduce 2 wide-spectrum bacteriocins, pediocin PA-1 and nisin A, at levels comparable to the respective parental strains. Previous studies have reported maximum pediocin yields of approximately 30% of that of P. acidilactici 347 in laboratory (Horn et al, 2004) or wild (Reviriego et al, 2005(Reviriego et al, , 2007 lactococcal strains that coproduce nisin and pediocin PA-1 through the leader exchange strategy. The synergistic effects of these 2 unrelated bacteriocins against foodborne pathogens and the beneficial effects of their coproduction (Hanlin et al, 1993;Mulet-Powell et al, 1998;Horn et al, 2004) can be exploited to extend their potential application in the dairy industry.…”
mentioning
confidence: 99%